Proprotein Convertase Subtilisin/kexin type 9 Inhibition in Cardiovascular Prevention - Ali, Ali; Costanzo, Pierluigi; Hoye, Angela (Current Pharmaceutical Design, 2018)
Elevated levels of Low Density Lipoprotein cholesterol (LDL-C) are directly associated with increased risk for atherosclerotic cardiovascular and cerebrovascular events. Statins have been used to control serum LDLC and this has translated into reduction in cardiovascular and cerebrovascular events. However, despite high dose statin therapy, LDL-C control may remain inadequate in some patients, particularly those with familial hypercholesterolemia. A new therapeutic approach has emerged in recent years with proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors. In this review, we describe the development and the use of this new class of drugs.
Keywords: PCSK9 inhibitors